Competitiveness Modelling In The Hotel Sector In Boyacá, Colombia - Pedro Ignacio Moya Espinosa (Migration Letters, 2021)
The purpose of this research is to analyze competitiveness in the hotel sector in Boyacá, with the aim of providing an effective tool for its promotion and strengthening. The research was oriented towards a causal approach, supported by quantitative methods, specifically modelling with Smart PLS (Partial Least Squares) - SEM (Structural Equation Models). Two instruments, each with 21 items, were administered to a population of 55 managers through a census, and to 384 guests through quota sampling. The results allowed validating the hypotheses and determining the impact of the independent variables (Internal and External Factors), as well as the mediating variables, on the dependent variable, i.e. competitiveness. The proposed model exhibited strong internal validity and offers favourable conditions for its application in other contexts and sectors. This research contributes significantly to the understanding of the factors that impact competitiveness in the hotel sector, providing a solid basis for future studies and, at the same time, offers practical guidelines for strengthening competitiveness in the hotel sector.